2014
DOI: 10.1111/1462-2920.12520
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal growth potential of rare lake water bacteria suggest their disproportional contribution to carbon fluxes

Abstract: We studied the seasonal growth potential of opportunistic bacterial populations in Lake Zurich (Switzerland) by a series of grazer-free dilution culture assays. Pronounced shifts in the composition of the bacterial assemblages were observed within one doubling of total cell numbers, from initially abundant Actinobacteria to other fast-growing microbial lineages. Small populations with growth potentials far above community average were detected throughout the year with striking seasonal differences in their res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 89 publications
4
58
0
Order By: Relevance
“…These results are particularly relevant because the contribution of different taxa to the uptake of C and P substrates greatly affects the energy and nutrient supply to aquatic food webs (Šimek et al ., 2005; Salcher et al ., 2007). Our findings agree with a recent study showing that in grazer‐free incubations, and particularly during periods of high organic matter loadings, rare taxa dominated bacterial community composition (Neuenschwander et al ., 2015). The authors suggested that the low abundance of these taxa at natural settings is controlled by bacterivorous grazing, implying that their biomass contributes substantially to the C channelled towards higher trophic levels.…”
Section: Discussionmentioning
confidence: 99%
“…These results are particularly relevant because the contribution of different taxa to the uptake of C and P substrates greatly affects the energy and nutrient supply to aquatic food webs (Šimek et al ., 2005; Salcher et al ., 2007). Our findings agree with a recent study showing that in grazer‐free incubations, and particularly during periods of high organic matter loadings, rare taxa dominated bacterial community composition (Neuenschwander et al ., 2015). The authors suggested that the low abundance of these taxa at natural settings is controlled by bacterivorous grazing, implying that their biomass contributes substantially to the C channelled towards higher trophic levels.…”
Section: Discussionmentioning
confidence: 99%
“…Rare soil taxa that were below detection not only responded to pulses of precipitation by blooming but also contributed to increased carbon dioxide and methane production, demonstrating that rare taxa collectively can contribute to ecosystem function (Aanderud et al 2015). Similarly, typically rare but fast-growing, cultivable taxa from Lake Zurich, Switzerland, could offer substantial contributions to carbon cycling (Neuenschwander et al 2015). A latitudinal analysis of marine bacterioplankton showed that fewer rare taxa are detectable in polar waters, possibly because these communities comprise fewer but more abundant taxa (Amend et al 2013).…”
Section: Raritymentioning
confidence: 99%
“…Notably, the classification of a microorganism as an oligotroph or a copiotroph is separate from the habitat in which it resides (Semenov 1991, but see Koch 2001 for an opposing definition); both oligotrophic and copiotrophic microorganisms can persist in both low-and high-productivity environments. Indeed, populations of each strategy may complement each other in their dynamics in seasonally fluctuating or heterogeneous environments (Neuenschwander et al 2015).…”
Section: Heterotrophic Strategiesmentioning
confidence: 99%
See 2 more Smart Citations